The Influence of Entrepreneurship Education and Income Expectations on Entrepreneurial Interest with Entrepreneurial Attitude as an Intervening Variable among Public Senior High School Students in East Jakarta - Sari, Desy Nia; Eryanto , Henry; Saptono, Ari (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study aims to examine the influence of Entrepreneurship Education and Income Expectations on Entrepreneurial Interest, with Entrepreneurial Attitude as an intervening variable among students at public senior high schools (SMA Negeri) in East Jakarta. The population of this study consists of students from public high schools in East Jakarta, with the accessible population being students from SMA Negeri 76 Jakarta and SMA Negeri 11 Jakarta. The research sample consisted of 180 students. The data collection method used was a questionnaire, and the data were analyzed using path analysis with the assistance of SPSS version 25. The results of the study indicate that: (1) There is a positive and significant influence of entrepreneurship education on entrepreneurial attitude among students in East Jakarta public high schools. (2) There is a positive and significant influence of income expectations on entrepreneurial attitude. (3) There is a positive and significant influence of entrepreneurship education on entrepreneurial interest. (4) There is a positive and significant influence of income expectations on entrepreneurial interest. (5) There is a positive and significant influence of entrepreneurial attitude on entrepreneurial interest. (6) There is a positive indirect effect of entrepreneurship education on entrepreneurial interest through entrepreneurial attitude. (7) There is a negative indirect effect of income expectations on entrepreneurial interest through entrepreneurial attitude.